Effect of Sodium Dodecyl Benzene Sulfonate Addition as Surfactant in Carbon Nanofluid for Quench Medium Application - Maulana Naufalino; Mohammad Ilham Daradjat; Ravanya Nabilla Ramadhani Parawansa; Benediktus Ma'dika; Ghiska Ramahdita; Sri Harjanto; Wahyuaji Narottama Putra (Jurnal Metalurgi dan Material Indonesia, 2018)
Nanofluids, which are fluids containing suspensions of nanoparticles, have been reported to have higher thermal conductivity than conventional fluid, e.g. water, oil, etc. Because of this characteristic, nanofluids are very attractive in heat transfer applications, such as quenching medium for heat treatment process. This unique characteristic is caused by the nanoparticles inside the fluid that have higher thermal conductivity, thus perform better on heat absorption and heat transfer. By varying the nanoparticles content in the fluid base, the cooling rate can be controlled in accordance with the desired characteristics of the material. Carbon is used as a nanoparticle because of the low cost and environmental friendly characteristics, but still have relatively high thermal conductivity. Unfortunately, carbon nanoparticle is highly hydrophobic. Therefore, surface modification is needed by using surfactant in the nanofluids. In this paper, Sodium Dodecyl Benzene Sulfonate (SDBS) was used as surfactant from 1, 3, and 5% in 100 ml water-based nanofluid with 0.5% volume carbon. The carbon powder used in this research was commercial grade, and ball-milled for 10 hours at 500 rpm to reduce the particle size. Commercially available household bodycare product which contain SDBS was used for surfactant source. Scanning Electron Microscope (SEM) showed that the particle size after milling were roughly 10 µm. Medium carbon steel, S45C, was heated at 1000°C for 1 hour, and then quenched using this nanofluid. Microstructure observation showed martensite phase formation after quenching. Hardness test confirmed this phase, showing hardness up to 949 HV after quenching using surfactant added nanofluid.